Alienation and Digital Labour—A Depth-Hermeneutic Inquiry into Online Commodification and the Unconscious - Steffen Krüger; Jacob Johanssen (tripleC: Communication, Capitalism & Critique)
At the core of this paper is a psychosocial inquiry into the Marxist concept of alienation and its applications to the field of digital labour. Following a brief review of different theoretical works on alienation, it looks into its recent conceptualisations and applications to the study of online social networking sites. Finally, the authors offer suggestions on how to extend and render more complex these recent approaches through in-depth analyses of Facebook posts that exemplify how alienation is experienced, articulated, and expressed online. For this perspective, the article draws on Rahel Jaeggi’s (2005) reassessment of alienation, as well as the depth-hermeneutic method of “scenic understanding” developed by Alfred Lorenzer (e.g. 1970; 1986).